ELECTRIC POWER EQUIPMENT AND ELECTRICAL ENERGY TECHNICAL OF DEVICES WASTE. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In recent years, the increasing cost of energy resources has necessitated significant transformations in energy accounting systems across various sectors, including industry, transportation, and housing. The demand for modern, highprecision metering devices to replace outdated and imprecise methods of measuring energy consumption has grown among consumers and suppliers alike. This shift underscores the importance of Automated Energy Control and Accounting Systems (AECAS), which streamline energy accounting and management processes. AECAS integrates advanced metering, data collection, and processing technologies to automate energy consumption monitoring, improve operational efficiency, and minimize human intervention. By employing telemetric and digital measurement devices, data transmission networks, and specialized software tools, AECAS provides reliable, accurate, and comprehensive energy data. This system enables consumers to optimize their energy usage,